Pengetahuan Kesiapsiagaan Bencana Pada Anak Usia Sekolah Sebelum dan Sesudah Diberikan Video Animasi Kesiapsiagaan Bencana - Mona Saparwati; Trimawati Trimawati; Fiki Wijayanti (Pro Health Jurnal Ilmiah Kesehatan, 2020)
The region of Indonesia is located between three tectonic plates namely Eurasian plate, the Pacific plate and Australia-Indies plate. These conditions lead to Indonesia to be proned of earthquakes, tsunamies, volcanic eruptions, and other types of geological disasters. Education for disaster is important to people's lives, to make disaster preparedness which is an absolute requirement for the development of disaster risk reduction. The purpose of this to study is to find out the difference between knowledge of disaster preparedness on high school students before and after given disaster learning.The design in this research method used pre-experimentaltype with pre test and post test in one group. The population on this research werestudents of SDN Candirejo 01 Ungaran as many as 125 students with research samples as many as 68 respondents taken by proportional random sampling technique. Instruments for disaster preparedness variable used questionnaire from LIPI. Univariate analysis test in the form of frequency distribution and percentage and used Wilcoxon bivariat test.The results showed studentâ€™s knowledge before the disaster learning is in less category as many as 31 students (51.1%) and after given disaster learning in good category as many as 37 students (55.5%). There is significant differences between knowledge of disaster preparedness before and after given disaster learning by using audio visual on students of SDN Candirejo 01 Ungaran (p = 0.000).Â